Low-phonon tellurite glass co-doped with Tm3+/Ho3+ ions for optical fibre technology - Zmojda, Jacek Mariusz; Kochanowicz, Marcin; Dorosz, Dominik (Photonics Letters of Poland, 2014)
In this paper the material and optical properties of tellurite glasses co-doped with Tm3+/Ho3+ ions were investigated. Near infrared luminescence at the wavelength of 2060 nm (5I7 -> 5I8) in holmium ions was obtained as a result of energy transfer between Tm3+ and Ho3+ ions. The energy transfer (ET) between Tm3+ -> Ho3+ ions was investigated pumping at 795 nm. As a result of optimization of rare earth concentration the best efficiency of energy transfer in fabricated glasses was obtained for molar composition 0.2mol%Tm2O3: 0.2mol%Ho2O3. Full Text: PDF References H. Gebavi, D. Milanese, G. Liao, Q. Chen, M. Ferraris, M. Ivanda, O. Gamulin, S. Taccheo, "Spectroscopic investigation and optical characterization of novel highlythulium doped tellurite glasses", Journal of Non-Crystalline Solids, 355 (2009) 548-555. CrossRef B.M. Walsh, "Review of Tm and Ho materials; spectroscopy and lasers", Laser Physics, 19 (2009) 855-866. CrossRef S.D. Jackson, Y. Li, "High-power broadly tunable Ho3+-doped silica fibre laser", Electron. Lett, 40 (2004) 1474?1475 CrossRef M. Wang, L. Yi, G. Wang, L. Hu, J. Zhang, "2um emission performance in Ho3+ doped fluorophosphate glasses sensitized with Er3+ and Tm3+ under 800 nm excitation Solid State Communications", 149 (2009) 1216-1220. CrossRef H. Lin, Y.Y. Zhang, E.Y. Pun, "Fluorescence investigation of Ho3+ in Yb3+ sensitized mixed-alkali bismuth gallate glasses", Spectrochimica Acta. Part A, Molecular and biomolecular spectroscopy, 71 (2008) 1547-1550 CrossRef Q. Nie, X. Li, S. Dai, T. Xu, Z. Jin, X. Zhang, "Energy transfer and upconversion luminescence in Tm3+/Yb3+ co-doped lanthanum?zinc?lead?tellurite glasses", Journal of Luminescence, 128 (2008) 135-141. CrossRef X. Shen ,Q. Nie, T. Xu, T. Peng, Y. Gao, "Green and red upconversion emission and energy-transfer between Er3+ and Tm3+ ions in tellurite glasses", Physics Letters A332 (2004) 101?106 CrossRef T. Förster, "Zwischenmolekulare Energiewanderung und Fluoreszenz", Ann. Physik 6(2) (1948) 55-59 CrossRef